Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1002/pon.2960010204
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depressive symptoms at different stages of malignant melanoma

Abstract: The HAD scale was used to assess anxiety and depressive symptoms in three groups of individuals visiting an oncology clinic, healthy persons with hereditary melanoma (group DNS), patients treated for cutaneous malignant melanoma stage I (group MMl), and patients with generalized disease (group MM2). No differences were found on the anxiety subscale, although MM2 scored higher than the other groups on two out of seven anxiety items. The depression subscale, and six out of seven items in this subscale showed hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
2
4

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 20 publications
(15 reference statements)
7
64
2
4
Order By: Relevance
“…A total of 15% were considered HAD anxiety 'borderline' or 'possible' cases and 12% fell into these categories for HAD depression. These values are comparable to those reported by Brandberg and co-workers (25) for patients at different stages of malignant melanoma ( 19% 'borderline' or 'possible' anxiety cases, and 8% 'borderline' or 'possible' depression). The numerical scale anxiety levels and reports on worries agree well with results from previous studies (18,19) performed on patients with a variety of cancer types at a point in time approximately 6 years after diagnosis and treatment.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A total of 15% were considered HAD anxiety 'borderline' or 'possible' cases and 12% fell into these categories for HAD depression. These values are comparable to those reported by Brandberg and co-workers (25) for patients at different stages of malignant melanoma ( 19% 'borderline' or 'possible' anxiety cases, and 8% 'borderline' or 'possible' depression). The numerical scale anxiety levels and reports on worries agree well with results from previous studies (18,19) performed on patients with a variety of cancer types at a point in time approximately 6 years after diagnosis and treatment.…”
Section: Discussionsupporting
confidence: 78%
“…The numerical scale scores were transformed to a category scale (none = 0, little = 1-3, moderate = 4-6, strong = 7-10) (cf. 5,25). Most of the patients (60%-83%) reported no anxiety before, during or after the visit.…”
Section: Anxietymentioning
confidence: 98%
“…A total of eight different factor structures have been suggested in the literature as providing the 'best fit' to the HADS item structure (1 unidimensional distress, 2 bidimensional consisting anxiety and depression, and 5 tridimensional consisting of anxiety depression and restlessness/agitation/negative-affectivity) [1,8,[28][29][30][31][32]. Furthermore, two bifactor structures were considered since this model has been shown to provide the best fit in other studies jointly assessing symptoms of anxiety and depression [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The few available comparative studies have revealed that mixed groups with primarily early-stage melanoma patients on average perform better as to quality of life than those with other malignancies. Stress requiring treatment has been ascertained in 10-45 % of melanoma patients [654][655][656][657][658][659]. With advanced disease, impairment of physical and role functions [660] as well as financial and professional problems emerged.…”
Section: Gcpmentioning
confidence: 99%